Site management and productivity in tropical plantation forests: workshop proceedings 16-20 February 1998, Pietermaritzburg, South Africa. - Nambiar, E.K.S.; Tiarks, A.; Cossalter, C.; Ranger, J. (Center for International Forestry Research, 1999)
These proceedings describe the experimental basis and preliminary results of the CIFOR project 'Site management and Productivity in Tropical Plantations'. The papers were presented at the second workshop off project partners held in Pietermaritzburg, South Africa, in February 1998. The research, which is underway at 17 sites in seven countries and involves scientists from 16 institutions, focuses on inter-rotation management. This phase between tree harvesting and replanting for the next rotation is a window of considerable risks as well as opportunities. It holds the potential for physical and chemical soil degradation, but also offers a chance to remedy past mistakes and introduce sound technology for improved long-term management of plantation soils. Although the species and the soil problems vary according to local conditions, all the experiments have been designed to provide knowledge that will benefit both the specific sites and our understanding of underlying processes of tree productivity.